The Impact of Europe's Individualism/Collectivism on the International Trade (European Journal of Marketing and Economics, 2019)
If we are to choose between two distinct statements, that the interest of the group prevails over the interest of the individual for the majority of people and that a minority of people in our world live in societies in which the interests of the individual prevail over the interests of the group, we can conclude, as Hofstede did, that there are two categories in which nations can fit: individualists and collectivists. The purpose of our study is to investigate the impact of this cultural dimension on the international trade of the European countries. Panel regression model with country fixed effects has been applied to the 21 years’ data (1997-2017. Based on prior studies conducted by Inglehart, the analysis of the World Values Survey, the cross-national values databases of Schwartz, Hofstede, Triandis, GLOBE, and Trompenaars, we proxied the individualism with three variables, i.e labor productivity index, higher education rate, and urban population growth rate. The findings of previous studies suggest that individualism has significant positive relationship with the imports and exports of Eastern European Countries, notably, Poland, Lithuania and Romania. Concurs with previous studies, our results show there is a significant positive relationship between individualism and international trade (both imports and exports).
Keywords: European Culture, International trade, Hofstede’s cultural dimensions, Individualism vs. Collectivism, Cultural complexity